Design and Synthesis of Novel Janus Dendrimers as Lipophilized Antioxidants - Pan, Junzhu; Ma, Lifang; Zhao, Yi; Zhao, Jing; Ouyang, Liang; Guo, Li (Synlett, 2013)
In the search for better antioxidants with more satisfactory lipophilicity, a series of Janus dendrimers that consisted of gallic acid and alkyl chains as the peripheral groups, were designed and synthesized. These dendrimers take advantage of a dendritic display to carry multi-antioxidants and multi-lipophilic moieties simultaneously. Consequently, the resulting dendrimers, which showed satisfactory lipophilicity and better antioxidant activity than the gallic acid monomer, are potential novel lipophilized antioxidant agents.
Keywords: Janus dendrimers; gallic acid; antioxidant; lipophilization; polyphenols